Improving Students' Basic Emotional Management Skills Through the Emoji Card Method in the Malaysia International Teaching Volunteer Program (LPPM Universitas HKBP Nommensen, 2025)
This review summarizes the literature discussing emotional management among children, particularly students in the Quranic Learning Center (Taman Pendidikan Al-Quran) in Kuala Lumpur, Malaysia, using the emoji card method. The ability to recognize, understand, and manage one's emotions and those of others greatly aids in building relationships and addressing life's challenges. Moreover, awareness of biases and self-emotions supports daily learning processes and enhances students' academic growth. The method employed for this community service was an experimental approach with a One-Group Pretest-Posttest design. The implementation stages included: (1) initial partner condition mapping, (2) introduction and administration of a pretest using a socio-emotional assessment sheet, (3) training using the